Nanometrology of field gradient using donor spins in silicon. (1st October 2018) - Gong, Pu; Pang, Hongliang; Yu, Hongyi; Yao, Wang
Abstract: We proposed a novel scheme for nanometrology of magnetic field gradient based on Kane's silicon quantum computer proposal. When the system is placed in an unknown magnetic field gradient, the inhomogeneous precession of the donor nuclear spins records the field gradient information to the phase pattern of donor nuclear spins. By adding AC voltage modulations on each A-gate to induce hyperfine-mediated electron-nuclear collective flip-flop process, we demonstrate that the gradient value can be obtained by tuning the modulation phases of the A-gates. Errors of the measurements of such scheme is discussed and estimated. It is also discussed that in presence of the external field with a known gradient, the same system is possible to be used to obtain the unknown displacement of donor locations.